Impact of the Balkan Wars (1912/13) on the Societies in South Slavic Lands of Austria-Hungary - Amir Krpić (Društvene i Humanističke Studije, 2024)
This paper discusses the immediate consequences that the Balkan Wars (1912-1913) had on the societies in the South Slavic lands of Austria-Hungary. It represents an attempt to summarize the previous results of research on various issues related to the consequences of the Balkan Wars in these lands individually. The focus was on finding common characteristics, as well as peculiarities regarding the impact of the wars on societies in the Slavic south of the Monarchy. In this sense, the focus of attention was on the national question, the political scene, the way of governing, and the economy. It stands out that the Balkan Wars were the spark that ignited the flame of nationalism in the south of the Monarchy, within the framework of the Yugoslav question. Foreshadowing a new era, these wars were for some an indication of the inevitability of reforming the Monarchy in a direction that would ensure a more favourable position for its Yugoslavs, and for others even an indication of its imminent destruction and Yugoslav unification on a broader basis. At the same time, the wars caused new or deepened existing crises in the lands to the south of the Monarchy, serving as an excuse for its authorities to introduce emergency measures or tighten existing restrictions. While in most of the South Slavic lands, the Austro-Hungarian government faced the united front of those forces that openly expressed their support for the Balkan allies, in Bosnia it greatly benefited from the growing political rift between the two dominant national communities and their political representatives. The wars left negative economic consequences in all lands, and by creating new circumstances, they enabled a different approach to solving the agrarian issue in Bosnia.